The The Integration of Generative AI in the Creative Industry of Visual Communication Design: An Analysis of Its Impacts, Ethical Challenges, and Work Originality - Iswanto, Rendy (Universitas Ciputra, 2025)
The emergence of Artificial Intelligence (AI) technology, particularly Generative AI, has brought significant changes across various sectors, including the creative industry—especially in the field of Visual Communication Design (VCD), which integrates technology, aesthetics, and communication. This study aims to analyze how Generative AI is integrated into the workflow of creative industry professionals, its impact on productivity and the creative process, as well as the challenges encountered. A qualitative research method was employed using a case study approach and in-depth interviews with creative practitioners in graphic design, photography, and multimedia production. The findings show that Generative AI helps accelerate production processes and opens new spaces for idea exploration yet also raises concerns regarding the originality of works and potential threats to certain creative professions. This study provides recommendations for optimizing the use of AI while maintaining ethical considerations and the essential role of humans in the creative process.